Modeling Gene-Environment Interaction for the Risk of Non-hodgkin Lymphoma - Zhang, Jiahui; Ye, Xibiao; Wu, Cuie; Fu, Hua; Xu, Wei; Hu, Pingzhao (Frontiers in Oncology, 2019)
Background Non-Hodgkin lymphoma (NHL) is one of the most common and deadly cancers. There is limited analysis of gene-environment interactions for the risk of NHL. This study intends to explore the interactions between genetic variants and environmental factors, and how they contribute to NHL risk. Methods A case-control study was performed in Shanghai, China. The cases were diagnosed between 2003 and 2008 with patients aged 18 years or older. Samples and SNPs which did not satisfy quality control were excluded from the analysis. Weighted and unweighted genetic risk scores (GRS) and environmental risk scores were generated using clustering analysis algorithm. Univariate and multivariable logistic regression analyses were conducted. Moreover, genetics and environment interactions (G x E) were tested on the NHL cases and controls. Results After quality control, there are 22 SNPs, 11 environmental variables and 5 demographical variables to be explored. For logistic regression analyses, 5 SNPs (rs1800893, rs4251961, rs1800630, rs13306698, rs1799931) and environmental tobacco smoking showed statistically significant associations with the risk of NHL. Odds ratio (OR) and 95% confidence interval (CI) was 10.82 (4.34-28.88) for rs13306698, 2.84 (1.66- 4.95) for rs1800893, and 2.54 (1.43- 4.58) for rs4251961. For G x E analysis, the interaction between smoking and dichotomized weighted GRS showed statistically significant association with NHL (OR= 0.23, 95% CI= (0.09, 0.61)). Conclusions Several genetic and environmental risk factors and their interactions associated with the risk of NHL have been identified. Replication in other cohorts is needed to validate the results.